Brachiaria establishment and haymaking in ILRI Nigeria demonstration plots - International Livestock Research Institute (International Livestock Research Institute, 2022)
From June–December 2021, the ILRI Nigeria team demonstrated to peri-urban farmers how to plant Brachiaria grass and process it into hay. The activity aimed to give a practical exhibition of haymaking from planting to harvest in humid regions of West Africa.28 Sept 2022